1992
DOI: 10.1021/jm00100a009
|View full text |Cite
|
Sign up to set email alerts
|

New bronchodilators. 1. 1,5-Substituted 1H-imidazo[4,5-c]quinolin-4(5H)-ones

Abstract: A series of novel xanthine-based tricyclic heterocycles in 1H-imidazo[4,5-c]quinolin-4(5H)-ones was designed, synthesized, and tested as potential active bronchodilators. Inhibition of the Schulz-Dale (SD) reaction-induced contraction in trachea and inhibition of antigen inhalation-induced bronchospasm in passively sensitized guinea pigs served as primary in vitro and in vivo assays, respectively. Simultaneous measurement of acute lethal toxicity (minimum lethal dose; MLD, po) in mice allowed determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…When compared the effect of bromo substituent on the quinazolinone ring of title compounds, it was found that non bromo analogues have shown potent anti-inflammatory activity than the bromo analogues. The order of activity in this series was non-bromo analogues (1-5) > monobromo analogues (11)(12)(13)(14)(15) > dibromo analogues (6)(7)(8)(9)(10).…”
Section: Carrageenan-induced Paw Edema In Ratsmentioning
confidence: 82%
See 3 more Smart Citations
“…When compared the effect of bromo substituent on the quinazolinone ring of title compounds, it was found that non bromo analogues have shown potent anti-inflammatory activity than the bromo analogues. The order of activity in this series was non-bromo analogues (1-5) > monobromo analogues (11)(12)(13)(14)(15) > dibromo analogues (6)(7)(8)(9)(10).…”
Section: Carrageenan-induced Paw Edema In Ratsmentioning
confidence: 82%
“…For example electronic withdrawing group (mainly bromo substitutions) enhanced the PDE1 inhibitory activity whereas non bromo analogues have shown less activity. The order of activity was dibromo analogues (6-10) > monobromo analogues (11)(12)(13)(14)(15) > non bromo analogues (1)(2)(3)(4)(5). The substituent over thiophene nucleus also led to significant variation in PDE1 inhibitory activity.…”
Section: Pde1 Inhibitory Activitymentioning
confidence: 98%
See 2 more Smart Citations
“…Imidazoles are more vital in many biological processes since they are present in many natural compounds. Many synthetic pyrimidine analogs are also known to exhibit a variety of therapeutic uses including antiviral [9], antimycobacterial [10], antitumor [11], anti-inflammatory [12], antidepressant [13], branchodilatory [14], antifungal activity [15], etc.…”
Section: Introductionmentioning
confidence: 99%